PERCEIVED USE OF METACOGNITIVE STRATEGIES BY EFL UNDERGRADUATES IN ACADEMIC READING - Rahman, Kasyfur (VELES Voices of English Language Education Society, 2020)
While investigations on metacognitive awareness in reading comprehension have yielded inconsistent results despite similar instruments, there is a need to expand the previous studies particularly into Indonesian tertiary EFL context in order to validate the findings. This paper seeks to quantitatively explore perceived use of metacognitive strategies in reading academic texts through an online questionnaire administered to 66 final year EFL undergraduates in an Indonesian university. Generally, the findings suggest moderate to high use of metacognitive strategies. More specifically, the findings demonstrate a high frequency of problem-solving strategies in comparison with the global and support strategies.  Least moderate perceived use of several strategies is likely to be influenced by the students? limited academic reading experience and limited reading schemata. Therefore, this research confirms the previous research that demonstrates problem-solving strategies as mostly perceived strategies by English nonnative students in their reading. The findings also advocate the need for the teaching of several strategies that demonstrate moderate frequencies yet highly needed for academic reading purposes.